A myogenic precursor cell that could contribute to regeneration in zebrafish and its similarity to the satellite cell. (24th May 2013) - Siegel, Ashley L.; Gurevich, David B.; Currie, Peter D.
<x xml:space="preserve">Abstract</x> The cellular basis for mammalian muscle regeneration has been an area of intense investigation over recent decades. The consensus is that a specialized self‐renewing stem cell, termed the satellite cell, plays a major role during the process of regeneration in amniotes. How broadly this mechanism is deployed within the vertebrate phylogeny remains an open question. A lack of information on the role of cells analogous to the satellite cell in other vertebrate systems is even more unexpected given the fact that satellite cells were first designated in frogs. An intriguing aspect of this debate is that a number of amphibia and many fish species exhibit epimorphic regenerative processes in specific tissues, whereby regeneration occurs by the dedifferentiation of the damaged tissue, without deploying specialized stem cell populations analogous to satellite cells. Hence, it is feasible that a cellular process completely distinct from that deployed during mammalian muscle regeneration could operate in species capable of epimorphic regeneration. In this minireview, we examine the evidence for the broad phylogenetic distribution of satellite cells. We conclude that, in the vertebrates examined so far, epimorphosis does not appear to be deployed during muscle regeneration, and that analogous cells expressing similar marker genes to satellite cells appear to be deployed during the regenerative process. However, the functional definition of these cells as self‐renewing muscle stem cells remains a final hurdle to the definition of the satellite cell as a generic vertebrate cell type.